Aplikasi TAM, Persepsi Risiko, dan Kepercayaan dalam Menjelaskan Niat Masyarakat Menggunakan Internet Banking - Sulastini, Ni Putu; Warmika, I Gde Ketut (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Internet banking is facility from bank to customers for anytime and anywhere banking activities. Intention people use internet banking in Indonesia is lower than the rapid use of internet. The aim of this research is to know influence of Technology Acceptance Model(TAM) which consists of perceived ease of use and perceived of usefulness, and additional perceived of risk and trust in intentions using internet banking in Denpasar. Data collected by questionnaires for 190 respondents by purposive sampling method. Analysis technique in this study was multiple linear regression analysis. The result was found each of the variables on TAM and trust has positive significant effect, while perceived of risk has negative significant effect on the intention to use internet banking. Keywords : technology acceptance model, perceive of risk,  trust, intention, internet banking
Keywords: technology acceptance model, perceive of risk, trust, intention, internet banking